2018
DOI: 10.1021/acs.chemrev.8b00070
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies for Modified Glycosphingolipids and Their Design as Probes

Abstract: The plasma membrane of cells contains a diverse array of lipids that provide important structural and biological features. Glycolipids are typically a minor component of the cell membrane and consist primarily of glycosphingolipids (GSLs). GSLs in vertebrates contain a multifarious assortment of glycan headgroups, which can be important to biological functions based on lipid-lipid and lipid-protein interactions. The design of probes to study these complex targets requires advanced synthetic methodologies. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 811 publications
(1,430 reference statements)
0
39
0
Order By: Relevance
“…Theg lobo-series glycans (Gb3, Gb4, and Gb5) were prepared by an OPME method using kinases (MtGalK and NahK) [15a, 21] for the production of sugar 1-phosphates,AtUSP to generate UDP-sugar nucleotides, [11,22] and glycosyltransferases (LgtC and LgtD) to construct glycosidic bonds. [9,10] Both CstI and PmST1 were used to assemble an a2,3-NeuAc moiety at the nonreducing-Gal/GalNAc end of Gb3, Gb4, and Gb5, respectively.Asshown in Scheme 1and Table S1 in the Supporting Information, extending the sugar chain resulted in higher yields of the products;y ields of 33 %, 41 %, and 43 %w ere obtained in the production of a3SGb3, a3SGb4, and a3SGb5 by CstI, respectively.H owever,G b3 and Gb4 were poor substrates for PmST1. Neither a2,3sialyltransferase preferentially formed the a-linkage to the nonreducing Gal/GalNAc,a nd this reaction was especially challenging with PmST1.…”
Section: Zuschriftenmentioning
confidence: 99%
See 3 more Smart Citations
“…Theg lobo-series glycans (Gb3, Gb4, and Gb5) were prepared by an OPME method using kinases (MtGalK and NahK) [15a, 21] for the production of sugar 1-phosphates,AtUSP to generate UDP-sugar nucleotides, [11,22] and glycosyltransferases (LgtC and LgtD) to construct glycosidic bonds. [9,10] Both CstI and PmST1 were used to assemble an a2,3-NeuAc moiety at the nonreducing-Gal/GalNAc end of Gb3, Gb4, and Gb5, respectively.Asshown in Scheme 1and Table S1 in the Supporting Information, extending the sugar chain resulted in higher yields of the products;y ields of 33 %, 41 %, and 43 %w ere obtained in the production of a3SGb3, a3SGb4, and a3SGb5 by CstI, respectively.H owever,G b3 and Gb4 were poor substrates for PmST1. Neither a2,3sialyltransferase preferentially formed the a-linkage to the nonreducing Gal/GalNAc,a nd this reaction was especially challenging with PmST1.…”
Section: Zuschriftenmentioning
confidence: 99%
“…[6] By treating NK cells with sialidase to remove NeuAc and disrupt the cis interactions,t he unmasked Siglec-7 can interact with DSGb5-Cer on the surface of the human renal cancer cell line ACHN,decreasing the cytotoxicity of the NK cells and promoting the metastasis and invasion of RCC. [8] Obtaining as ufficient amount of pure DSGb5 is key to elucidating its mechanism of action and to further develop cancer immunotherapies.C larifying the binding activities of sialylated globo-series glycans and the effect of the NeuAc position on their interactions with Siglec-7 is also of great interest.Thee nzymatic and chemoenzymatic syntheses of globoseries glycans,such as Gb5, SSEA-4, and Globo H, have been reported by several research groups, [9][10][11] but no method has been reported for the synthesis of DSGb5. DSGb5 has aunique glycan structure with two NeuAcs as a2,3-and a2,6linkages on the nonreducing-end galactose (Gal) and Nacetylgalactosamine (GalNAc), respectively,o fG b5 (Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ganglioside derivatives containing radioactive, fluorescent, paramagnetic, or photoreactive tags have been successfully employed in studies of incorporation into cells, in studies of their distribution in membranes as well as processes occurring on them, and in investigation of their metabolic fate and intracellular trafficking. For an overview, see refs . The focus of this Review will be placed on semisynthetic methods to generate ganglioside probes with labels in their sialooligosaccharide or ceramide moieties or both with emphasis on monosialogangliosides.…”
mentioning
confidence: 99%